SOLIDARITAS SOSIAL DI KALANGAN LAKI-LAKI FEMININ: STUDI KASUS PADA KOMUNITAS A+ ORGANIZER - Ikhsan, Rizal; Erianjoni, Erianjoni; Khaidir, Afriva (Sawwa: Jurnal Studi Gender, 2019)
This study aims to analyze social solidarity among feminine males, case studies on community A+ Organizer in Padang West Sumatera. This study was analyzed with the theory of social solidarity by Emile Durkheim. This research was conducted with a qualitative approach, with the type of research case study. The results found that there were two forms of social solidarity among the feminine male of the A+ Organizer community: 1) Mutual help such as: giving work, cooperation, and empowerment. 2) Collective activities in the form of together gathering such as: hanging out and regular social gathering. Factors that underlie the formation of social solidarity among feminine men in the A+ Organizer community: 1) The similarity of fate. 2) Interdependence.